A descriptive study assessing the infodemic medical students faced during COVID-19 pandemic - HIDIROĞLU, SEYHAN; KARAVUŞ, MELDA (My University, 2023)
With COVID-19, a new pandemic on worldwide basis emerged. An infodemic is a rapid and far-reaching spread of both accurate and inaccurate information about certain issues. Misinformation and disinformation can spread like a virus from person to person and affect people like a disease. The aim of this descriptive study was to assess the infodemic the medical students faced during COVID-19 pandemic. Second (n = 266) and third (n = 242) graders from a medical school in Istanbul, Tu¨rkiye were the study population. The study was completed with a total of 181 participants, 98 students from second grade and 83 from third grade who accepted to be included in the study in February 2022 while the COVID-19 pandemic was still continuing. A 5 point scale lickert type questionnaire was prepared and applied by the researchers to measure how much and particularly on which aspects the participants faced infodemic. Nearly half of the participants (47.5%) believed that they ‘almost always thought there was a COVID-19 infodemic’. As the most important causes of this infodemic the participants stated were ‘It is a new virus ‘ (31.5%) and ‘It affects daily routine life’ (31.5%). Around 40.9 % of the participants believed that the COVID-19 infodemic ‘adversely affected their health,’ 23.2% reporting low-mood and 15.5% anxiety. Around 52.5% of the participants stated that the COVID-19 infodemic had a negative impact on their general learning process at school. Additionally, 69.9% of the participants declared that they may not have shared anything that might have been the cause of any infodemic during the pandemic. Health authorities and educators should be aware that infodemic exists freely, adversely affecting health and education.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)